Evaluation of Growth Hormone Therapy in Seven Chinese Children With Familial Short Stature Caused by Novel ACAN Variants - Sun, Jie; Jiang, Lihong; Liu, Geli; Ma, Chen; Zheng, Jiaqi; Niu, Lele (Frontiers in Pediatrics, 2022)
Objective: ACAN gene variants are an important cause of familial short stature (FSS). Appropriate growth-promoting therapies effectively improve the patient height. Here, we report a therapeutic assessment of cases of seven families of FSS patients with heterozygous ACAN variants. Our findings provide a valuable theoretical basis for the clinical diagnosis and treatment of this disease. Methods: From December 2020 to June 2021, 32 FSS patients were examined in Tianjin Medical University General Hospital (Tianjin, China) by whole-exome sequencing to determine whether ACAN variants were present. Their clinical data were summarized and scrupulously analyzed. Results: We found seven novel heterozygous ACAN variants: c.1051 + 2T > A, c.313T > C (p.S105P), c.2660C > G (p.S887X), c.2153C > A (p. T718K), c.7243delG (p.D2415Tfs*4), c.2911G > T (p.G971X), c.758-7T > C. All seven patients had proportionate short stature and mild skeletal dysplasia. Endocrine examination results were normal. Only one of the patients had an advanced bone age (1.1 years older than chronological age), whereas the other patients had normal bone ages. All of them had a family history of short stature, with or without osteoarthritis or intervertebral disc disease. All seven patients accepted treatment with recombinant human growth hormone (rhGH) and were regularly followed up. One patient did not come at the follow-up visit. The height of the remaining six patients before and after the treatment was -2.89 ± 0.68 SDS, -1.91 ± 0.93 SDS, respectively, with a treatment course of 1.85 ± 1.91 years. A good therapeutic response was observed in all of them. Conclusions: In this study, seven novel heterozygous variants in ACAN were discovered, which expanded the spectrum of the already established ACAN pathogenic variants. In FSS cohort, the proportion of ACAN variants accounted was large. The treatment with rhGH effectively increased the patient height, but further studies with longer follow-up periods and more extensive observations are required to elucidate the long-term effect.